The Effect of Progressive Relaxation Techniques on Anxiety Levels in Schizophrenic Patients - Esse Puji Pawenrusi; Suarni Suarni; Hardianti Hardianti; ST. Nadia Astuti (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Schizophrenia is a disease that affects the brain and causes strange thoughts, perceptions, emotions, movements and behaviors . Schizophrenia is not a single disorder but is a syndrome with many causes. In Indonesia, the number of patients suffering from schizophrenia is around 6.7% with the highest prevalence in Bali (11.1%), the Special Region of Yogyakarta (10.4%), West Sumatra (9.1%) and South Sulawesi (8.8%). ). The purpose of this study was to determine the effect of relaxation techniques on the level of anxiety in Schizophrenic patients. This type of research is pre-experimental with a one-group pre-test and post-test design. The population in this study were patients suffering from schizophrenia with a total sample of 10 people in 2019. The sampling technique used was purposive sampling technique . The results of the study using the Wilcoxon signed rank test , obtained a value of (p = 0.003) <(α = 0.05), this means that there is a significant influence between progressive relaxation techniques on anxiety levels in schizophrenic patients in the work area of Karuwisi Health Center Makassar City. The conclusion of this study is that there is an effect of progressive relaxation techniques on anxiety levels in schizophrenia patients in the work area of Karuwisi Health Center Makassar City. It is hoped that from the results of this study, progressive relaxation therapy can be applied and improved as an exercise to reduce patient anxiety.